Use of a Rotating Biological Contactor for the Removal of Nitrogenous Compounds from Gold Mill Effluent - A. Kapoor; P. Béedard; L. Morin; A. Kuiper; S. Mortazavi; Gould. W. D. (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
The degradation of thiocyanate in a simulated gold mill effluent was studied using a laboratory scale rotating biological contactor (RBC). Complete SCN- removal was obtained at temperatures of 8 and 12°C, and a hydraulic retention time of approximately 3.3 h. The NH4+ produced by thiocyanate hydrolysis was oxidized by nitrifying bacteria to NO2 and NO3-. The HS- produced by thiocyanate hydrolysis was chemically and biologically oxidized to elemental S, which was subsequently biologically oxidized to sulfate. Incomplete sulfur oxidation occurred in the RBC, particularly at 8°C and elemental sulfur deposition was observed on the RBC disks. The RBC feed exhibited toxicity to rainbow trout but the RBC was effective in removing the acute toxicity of thiocyanate.